Η ΑΛΚΗΣΤΙΣ ΤΟΥ ΕΥΡΙΠΙΔΗ ΑΠΟ ΤΟ ΔΗ.ΠΕ.ΘΕ. ΒΟΛΟΥ (1995): Η ΚΟΥΚΛΑ ΩΣ ΠΑΡΑΣΤΑΣΙΑΚΟ ΜΕΣΟ [EURIPIDES’ ALCESTIS FROM THE MUNICIPAL AND REGIONAL THEATRE OF VOLOS (1995): PUPPETS AS A PERFORMANCE/STAGE SYSTEM] - Papadopoulos, Simos; Basoucou, Lina (ΠΑΡΑΒΑΣΙΣ/PARABASIS, 2025)
The main objective of this paper is to define and interpret the characteristics and uniqueness of the performance of Euripides’ play Alcestis by the Municipal and Regional Theatre of Volos in 1995, directed by Lydia Koniordou. It focuses on the use of full-body puppets, through which the director aims to highlight the play’s enigmatic nature and unify its contrasts, as well as to propose a specific staging of ancient drama based on puppets. According to the director, puppets as full- body masks underline the meanings and poetic essence of the play and give actors the opportunity to explore a new theatrical language, which leads them to simplicity. Additionally, the primary and secondary codes of the performance are briefly analyzed in the paper, with the use P. Pavis’ questionnaire as a methodological tool. Finally, the reception and evaluation of the performance by the critics are presented.